Is It Only Possible to Write a Short History of Kosovo? (KULT_online, 2009)
Oliver Jens Schmitt published the first history of Kosovo in German, which contains an excellent overview of Kosovo within the Roman, Byzantine, Serbian and Ottoman Empires, as part of Serbia and the different Yugoslavias, up to its status as a UN protectorate and its independence in 2008. In highly detailed chapters he conveys the living environment, the impact of religion, languages and migrations in this part of Europe and the structures affected by various empires and the south Slavic Yugoslavias. His book is meant to answer Serbian and Albanian myths about Kosovo and was developed in arguments with his Albanian and Serbian students.